Pengaruh Model Pembelajaran Inkuiri Terbimbing Berorientasi Tri Kaya Parisudha Terhadap Motivasi Dan Hasil Belajar IPAS Siswa Kelas VI Gugus II Kecamatan Klungkung - Lili Absari, I Gusti Ayu Komang (Jayapangus Press, 2025)
The issue of low motivation and learning outcomes in IPAS among sixth-grade students highlights the need for the implementation of an effective and character-based learning model, one of which is the Guided Inquiry model oriented towards Tri Kaya Parisudha. This study aims to determine the influence of the Guided Inquiry Learning Model oriented toward Tri Kaya Parisudha on motivation and IPAS learning outcomes of sixth-grade students in Cluster II of Klungkung District. This is a quasi-experimental study with a population consisting of all sixth-grade students in Cluster II of Klungkung District, totaling 196 students. The sample was selected using a random sampling technique. The sample of this study consisted of two classes: 33 students from SD Negeri 2 Akah as the experimental group and 32 students from SD Negeri 2 Semarapura Kangin as the control group. The research procedure involved three stages: preparation, implementation, and final phase of the experiment. Data were analyzed using MANOVA statistical testing. The results showed that: (1) there was a significant difference in learning motivation between students who followed the Guided Inquiry Learning Model oriented toward Tri Kaya Parisudha and those who followed conventional learning methods, with F = 143,864 and P<0,05; (2) there was a significant difference in IPAS learning outcomes between students taught using the Guided Inquiry Learning Model oriented toward Tri Kaya Parisudha and those taught using conventional methods, with F = 21,490 and P<0,05; (3) the implementation of the Guided Inquiry Learning Model oriented toward Tri Kaya Parisudha significantly influenced both motivation and IPAS learning outcomes of sixth-grade students in Cluster II of Klungkung District, with F = 74,030 and P<0,05.